The Power of Woman in Weiner’s Little Earthquakes - Andi Inayah Soraya (Hasanuddin University, 2018)
This research aimed to explain the power of women as a good wife and mother to face many problems in their life. It applies psychological Maslow’s theory, who proposes five steps of Hierarchy of Needs covering Psychological Needs, Safety Needs, Belongingness and Love Needs, Esteem Needs, and Self-Actualization. This research used descriptive qualitative method which used to analysis and explained how the psychological theory was applied in literary work focused on character analysis in this novel. The data in this research were taken from the dialogue and narration of the novel. The finding of analysis indicates that there are four mothers struggling to fulfill their needs in life. They are Becky, Kelly, Ayinde, and Lia. Based on the novel, those of characters have a lot of problems in their life. Not only problems, as human they also have kind of needs. To analyze their needs, the researcher connected with Hierarchy of needs by Maslow and found that they can fulfill all the steps start from Psychological, Safety, Belongingness, Esteem, and the high step is Self-Actualization. In spite of they need struggling which is not easy. But from their intention, support from each other called sisterhood, and love form people around them, they can solve their problem and fulfilled their needs.